Impact of the 2015 Migration Crisis on German Food Security - N. S. Ivannikov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
The article considers some social and political consequences of the migration crisis of 2015 in the Federal Republic of Germany, as well as its impact on food security in the country. In order to as- sess the latter, the statistical data related to socioeconomic factors important for food security were analyzed. Both the problems faced by migrants and their positive contribution to the agricultural sector, as well as the methods taken by Germany to improve the situation of migrants were high- lighted. The most important factor influencing food security in the conditions of sharp population growth caused by the migration crisis is adaptation, since both the further involvement of migrants in the economic life of the country and their further prosperous existence depend on its success. The effectiveness of measures taken by the German government for adaptation of migrants ensured a significant contribution to the preservation of the former level of food security in the changed conditions of the state.